2020
DOI: 10.3389/feart.2020.00054
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Contrasted Weather Conditions on CDOM Absorption/Fluorescence and Biogeochemistry in the Eastern Lagoon of New Caledonia

Abstract: New Caledonia (Southwest Pacific), like all tropical Pacific Island countries, is impacted by weather events, climate change, and local anthropogenic forcing. Strong erosion of particles and dissolved organic matter (DOM) from ultramafic rocks, associated with trace metals dissemination (i.e., nickel, manganese and cobalt), potentially affects lagoon waters and coral reefs surrounding the main island. The CALIOPE (CALedonian Inherent Optical PropErties) cruises were performed along the Eastern Lagoon of New Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 104 publications
(148 reference statements)
3
16
0
Order By: Relevance
“…Brownish-colored water is likely to have a high carbon load from the humic substances found in plants and soil. The organic carbon load from soil sediment runoff explains the acidic properties of the waters and the resulting yellow-brown coloration [14,15]. DOM occurs naturally in many forms such as fatty acids, carbohydrates, amino acids, hydrocarbons, fulvic acids, humic acids, viruses, and clay-humic metal complexes [10] and has both allochthonous and autochthonous origins [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brownish-colored water is likely to have a high carbon load from the humic substances found in plants and soil. The organic carbon load from soil sediment runoff explains the acidic properties of the waters and the resulting yellow-brown coloration [14,15]. DOM occurs naturally in many forms such as fatty acids, carbohydrates, amino acids, hydrocarbons, fulvic acids, humic acids, viruses, and clay-humic metal complexes [10] and has both allochthonous and autochthonous origins [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Allochthonous DOM is linked to degraded organic materials of terrestrial origin while autochthonous DOM arises from in-situ biological activities [13,14] such as phytoplankton exudation and lysis, animal excretion, and fragments or cadavers derived from biogenic sources [10,[17][18][19][20]. A fraction of DOM contains chromophores that strongly absorb short-wavelength light ranging from ultraviolet (UV) to blue of the electromagnetic spectrum [14][15][16], hence the term chromophoric dissolved organic matter (CDOM). CDOM can be characterized by its absorbance in the UV-visible domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study by Dupouy et al (2020) deals with the identification of the origin of DOC compounds in the coastal waters in and around the Eastern Lagoon of New Caledonia and examines its relationships to environmental forcing. Different biologicallyderived DOC in the water column of the lagoon showed that the humic-like components are particularly influenced by rainfall and terrigenous inputs, both variables that are strongly affected by global warming.…”
mentioning
confidence: 99%
“…Inter-related and spatially variable pressures including sea level rise, increased storminess, altered precipitation regime, varying continental runoff and increasing temperature are impacting these ecosystems at regional scales (Ward et al, 2016); but the intensity of the response seems site-specific (Godoy and Lacerda, 2015) and species-specific (McKee and Rooth, 2008;Ramachandran et al, 2020). Interactions with local anthropogenic drives, in particular damming, basin diversion, and eutrophication, also modify the intensity of the ecosystems' response, either favoring or hampering adaptability (Dupouy et al, 2020;Lacerda et al, 2020). The biogeochemistry of tropical coastal ecosystems is affected by the interaction between multiples stressors of local, regional, and global scales.…”
mentioning
confidence: 99%